Power and distribution transformers : practical design guide - Nair, K. R. M. (Boca Raton, FL : CRC Press, 2021)
This book is based on the author's50+ years experience in the power and distribution transformer industry. The first few chapters of the bookprovide astep-by-step procedures of transformer design. Engineers without prior knowledge or exposure to design can follow the procedures and calculation methods to acquire reasonable proficiency necessary to designing a transformer. Although thetransformer is a mature product, engineers working in the industry need to understandits fundamentals oand design to enable them to offer products to meet the challenging demandsof the power system and the customer. This book can function as a useful guide for practicing engineers to undertake new designs, cost optimization, design automation etc., without the need for external help or consultancy. The book extensively covers the design processes with necessary data and calculationsfrom a wide variety of transformers, including dry-type cast resin transformers, amorphous core transformers, earthing transformers, rectifier transformers, auto transformers, transformers for explosive atmospheres, andsolid-state transformers. The other subjects covered include, carbon footprint salculation of transformers, condition monitoring of transformers and design optimization techniques. In addition to being useful for the transformer industry, this book can serve as a reference for power utility engineers, consultants, research scholars, and teaching faculty at universities.
OCLC-licensed vendor bibliographic record.
Keywords: Electric power distribution; Electric power systems -- Design and construction; TECHNOLOGY / Electricity